PENGARUH STRATEGI SEGMENTATION, TARGETING DAN POSITIONING TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE (STUDI KASUS RIZQY MOBILE & COMP GRESIK) - Farida, Nur (Fakultas Ekonomi Universitas Gresik, 2019)
This study aims to examine and prove the effect of the strategy of segmentation, targeting and positioning on mobile purchasing decisions in Rizqy mobile & comp Gresik. This study uses a quantitative approach with multiple linear regression analysis with the data processed is segmentation, targeting, positioning and purchasing decisions. The number of samples taken 75 respondents and data collection was done by distributing questionnaires. The results showed that all independent variables segmentation, targeting and positioning partially had an influence on the increase in mobile purchasing decisions in Rizqy mobile & comp Gresik. The strategy of segmentation, targeting and positioning simultaneously has a positive and significant effect on mobile purchasing decisions on Rizqy mobile & comp Gresik.DOI 10.5281/zenodo.3629917